CONSIDERATIONS ABOUT THE INSTITUTIONALIZATION OF THE ELDERLY IN NATAL, RN (Fiep Bulletin - online, 2011)
Introduction: The question of aging in current society is increasingly important, resulting mainly from the decrease in general mortality and child bearing. This has led to an increase in the elderly population worldwide, and a sharp rise in social science, political and medical studies on the aging process, in addition to greater exposure of the topic in the international television and print media. Objective: Describe the aspects related to the institutionalization of the elderly in the city of Natal, Brazil. Material and Methods: Descriptive and exploratory study using a literature review of Scielo and Lilacs databases between December 2008 and July 2009. Results and Discussion: The accelerated aging process in Brazil poses new challenges to Brazilian society under a scenario of profound social, urban, industrial and family transformations. A new type of family has emerged, which, associated to the increase in the elderly population and the rising demand for this type of care facility, has led to the emergence of Long-Term Care Facilities (LTCFs) for the elderly. These are certainly not the best locations, nor the best care model for this population. However, this type of facility has increased significantly in Brazil, and public protection policies for seniors have been recognized and established to regulate their operation. Conclusion: Therefore, strategies capable of promoting quality aging must be created "given that the institutions will continue to be important housing facilities for the near future", and that the institutionalized elderly today are citizens with rights to quality care.
Keywords: Elderly; Human Aging; Long-Term Care Facility